Foraging Relationships Between Elephants and Lantana camara Invasion in Mudumalai Tiger Reserve, India. (March 2014) - Wilson, Gaius; Gruber, Monica A.; Lester, Philip J.
Abstract Lantana camara is a widespread exotic invasive species in India, capable of dominating and displacing native forage species. We investigated whether L. camara was associated with variation in elephant foraging behavior in Mudumalai Tiger Reserve, India. The behavioral responses of elephants to L. camara were assessed from feeding and stepping rates. Elephants were never observed to feed on L. camara, but rather fed on grass and browse present within and around L. camara patches. A multiple regression analysis showed that feeding rates were negatively associated with L. camara invasion (F1, 55 = 4.26, R2 = 0.07), but not stepping rates. Instead, grass cover and browse density were associated with stepping rates (F2, 55 = 11.16, R2 = 0.30). Path analysis indicated that the total effect of L. camara on feeding rates was 11 percent (β = −0.24) less than the direct negative association (β = −0.27) owing to a positive indirect association of L. camara with feeding rates through grass cover and browse density (β = 0.03), while stepping rates were negatively associated with grass cover (β = −0.39) and positively associated with browse density (β = 0.38). Our results indicate that L. camara appears capable of modifying feeding rates of elephants, likely through a loss of grass areas due to L. camara invasion. Experimental work is needed to test for causal relationships among the variables we measured, to enhance our understanding of how invasive weeds modify elephant behavior.